2012
DOI: 10.3354/ame01553
|View full text |Cite
|
Sign up to set email alerts
|

Virus-driven nitrogen cycling enhances phytoplankton growth

Abstract: Viruses have been implicated as major players in aquatic nutrient cycling, yet few data exist to quantify their significance. To determine the effect of viruses on ammonium regeneration by bacteria, experiments were carried out in the oligotrophic Indian Ocean and productive False Creek, Vancouver, Canada. Bacteria were concentrated and then diluted with virus-free water to reduce virus abundance, or with virus-replete water to restore natural virus abundances. Virus-replete treatments showed increased ammoniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 28 publications
8
81
0
Order By: Relevance
“…More generally, multiple groups have reported that viral lysis can stimulate the productivity of nontargeted populations in the short term (Middelboe et al, 1996;Gobler et al, 1997;Middelboe et al, 2003;Poorvin et al, 2004;Weinbauer et al, 2011;Shelford et al, 2012). Here, such effects are shown to be consistent with anticipated nonlinear feedbacks and nutrient dynamics of a multitrophic surface microbial ecosystem model over the long term, including both inorganic and organic nutrient pools.…”
Section: Viral Effects On Ecosystem Functioningsupporting
confidence: 70%
See 1 more Smart Citation
“…More generally, multiple groups have reported that viral lysis can stimulate the productivity of nontargeted populations in the short term (Middelboe et al, 1996;Gobler et al, 1997;Middelboe et al, 2003;Poorvin et al, 2004;Weinbauer et al, 2011;Shelford et al, 2012). Here, such effects are shown to be consistent with anticipated nonlinear feedbacks and nutrient dynamics of a multitrophic surface microbial ecosystem model over the long term, including both inorganic and organic nutrient pools.…”
Section: Viral Effects On Ecosystem Functioningsupporting
confidence: 70%
“…Such estimates were used B15 years ago to hypothesize that viruses may increase the flux of organic matter through ocean ecosystems when compared with idealized ecosystems without viruses (Fuhrman, 1999;Wilhelm and Suttle, 1999). This hypothesis is supported by manipulative experiments in which viral release of organic matter can have a stimulatory effect on the growth of nontargeted microbial populations (Middelboe et al, 1996;Gobler et al, 1997;Middelboe et al, 2003;Poorvin et al, 2004;Weinbauer et al, 2011;Shelford et al, 2012). However, even if one population is stimulated by the lysis of cells from another population in the short term, the same population may also be susceptible to lysis by other viruses in the community.…”
Section: Introductionmentioning
confidence: 71%
“…Besides the already mentioned high levels of viral abundance and infection on bacteria, infection of phytoplankton is also common during intense episodes of coastal algal bloom (Proctor and Fuhrman, 1991;Yau et al, 2011;Shelford et al, 2012;Hasumi and Nagata, 2014;Stock et al, 2014). Consequently, viral lysis of phytoplankton can significantly affect the partitioning and biological cycling of elements such as C, N, P, Si, and Fe (Gobler et al, 1997), and the potential consequences of viral infection on nutrient cycling has been extensively discussed ever since (Bergh et al, 1989;Heldal and Bratbak, 1991;Proctor and Fuhrman, 1991;Suttle et al, 1991).…”
Section: Viruses and Phytoplankton Mortalitymentioning
confidence: 99%
“…Today the roles of viruses are still a recurrent topic and the study of the microbial loop is far from exhausted (Middelboe et al, 2003;Sandaa, 2008;Ory et al, 2010;Yau et al, 2011;Magiopoulos and Pitta, 2012;Shelford et al, 2012;Xu et al, 2013;Brum et al, 2014;Hasumi and Nagata, 2014;Stock et al, 2014;Liu et al, 2015). Still, viruses are sometimes neglected (e.g., Follows and Dutkiewicz, 2010;Salihoglu et al, 2013), and only a few attempts have been made to model the details of bacterial and phytoplankton viral-induced cell lysis.…”
Section: Current State Of Modelingmentioning
confidence: 99%
“…From the standpoint of characterizing the influence of virus activity on ocean biogeochemistry, most studies have focused on characterizing the bulk material properties of lysate DOM (for example, total C, N, Fe, Se; see Gobler et al, 1997;Bratbak et al, 1998;Poorvin et al, 2004;Lønborg et al, 2013) or monitoring a few select molecules (for example, dimethyl sulfide, acrylate) or compound classes, such as amino acids and carbohydrates (see, for example, Weinbauer and Peduzzi, 1995;Middelboe and Jorgensen, 2006;Shelford et al, 2012). In general, these studies reported increases in these molecules in lysates (see, for example, Poorvin et al, 2004;Lønborg et al, 2013) and have hypothesized that viral lysates are rich in free and combined amino acids (Middelboe and Jorgensen, 2006) and may be an important source of labile organic nitrogen (Shelford et al, 2012).…”
Section: Introductionmentioning
confidence: 99%